Pengurangan Bullwhip Effect dengan Metode Vendor Managed Inventory - Fenny Rubbayanti Dewi; Annisa Kesy Garside (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2015)
Information distortion caused PT Multi Sarana Indotani got higher demand than the distributor. Demand variability in each echelon of the supply chain (bullwhip effect) may occur due to lack of demand stability that the producer had difficulty in determining the amount of production. One of the collaboration methods that can be applied to overcome the information distortion as causes of the bullwhip effect is vendor managed inventory, where the needs of distributor and retailers monitored and controlled by the producer. In this case, vendor managed inventory applied to two echelons, producer, and distributor.